ANALISIS PENGARUH PERKAWINAN DIBAWAH UMUR TERHADAP TINGKAT PERCERAIAN DI KOTA JAMBI - Suzanalisa Suzanalisa (Universitas Batanghari Jambi, 2013)
Marriage is a way to realize a family or household happy and eternal based on God . So the husband and wife in running a successful marriage requires maturity both physically and mentally responsibility to realize the ideal plots in married life tangga.Perkawinan minors run by married couples formed of characteristics that adolescents under 18 years of emotional instability , feelings discharged from overhaul of the views and instructions of life , attitudes and challenging parents opposed the match-making or decision of the parents in determining the choice of life , anxiety for a lot of things to be desired but the inability and limitations on yourself , so that the upheavals that comes from within oneself one partner husband and wife leave liability , discord , physical harm , moral , sociological disability , either as a punishment or as husband and wife so beakhirnya marriage in divorce .Keyword : Marriage, underage, divorce